P53 Regulation upon Lipid Peroxidation and Ferroptosis for Intervention against Atherogenesis - Zhao, Yuanqin; Deng, Wei; Wang, Zhaoyue; Wang, Yanxia; Zheng, Hongyu; Deng, Nianhua; Zhou, Kun; Ren, Zhong; Jiang, Zhisheng (Current Medicinal Chemistry, 2025)
Tumor protein 53 (P53), as an intracellular regulator of antioxidant responses, participates in the expression of antioxidant defense and lipid metabolism as well as the synthesis of genes in cells. The balance of oxidation and reduction can be disrupted by many pathological conditions, and the role of the antioxidant system in protecting the equilibrium state from pathological effects, such as reactive lipids, is crucial. In particular, the excessive accumulation of lipid peroxidation products is a key factor driving the occurrence and development of various diseases. Ferroptosis is an iron-dependent, lipid peroxidation-driven cell death cascade reaction, which has become a key research area in cardiovascular diseases. Atherosclerosis (AS) is a pathological change caused by lipid metabolic disorder, inflammatory response, and endothelial cell injury, and is the most common cause of cardiovascular disease. This review briefly outlines lipid peroxidation and key components involving ferroptosis cascade reactions, summarizes and emphasizes the role of P53-related signaling pathways in mediating lipid peroxidation and ferroptosis, and focuses on the known P53 target genes that regulate these pathways, as well as explores the possibility of P53 intervention in the treatment of AS by regulating lipid peroxidation and ferroptosis processes.
Keywords: ferroptosis